Excision of giant mature teratoma of the adrenal gland in a 1-year-old girl - Diego Eduardo Rey-Rodriguez; Jonathan Humberto Hidalgo-Salas; Jorge Justo Valdes-Gomez; Diana Mercedes Mora-Flores (Elsevier, 2021)
The mature teratoma is a germ cell tumor, characterized by the presence of mature tissue of two or more layers of germ cells. Mature teratomas of retroperitoneal localization are rare, and the cases reported in adrenal localization are even rarer. In this publication, we present the case of a 1-year-old girl, who attended a Medical Centre in Perú, for presenting a giant tumor at the level of the left adrenal gland associated with abdominal distension and difficulty standing.The patient underwent tumorectomy and adrenalectomy by open surgery and the pathological diagnosis was mature Teratoma of the left adrenal gland.A search was made by published cases of mature teratoma of the adrenal gland in pediatric patients, under 18 years of age. There were 13 cases reported to date, of which 8 cases (61.5%) were women, the most frequent location was the right adrenal gland (61.5%), and the range of tumor diameter was between 3.0 cm at 12.0 cm, with a mean of 8.0 cm. All cases were metabolically silent, the main symptoms were pain and abdominal distension.